International peacebuilding and local involvement a liberal renaissance? - Simangan, Dahlia; Taylor & Francis (Online service). (London New York Routledge, Taylor & Francis Group, 2019)
"This book interrogates the common perception that liberal peace is in crisis and explores the question: can the local turn save liberal peacebuilding? Presenting a case for a liberal renaissance in peacebuilding, the work interrogates the assumptions behind the popular perception that liberal peace is in crisis. It re-examines three of the cases that ignited the debate - Cambodia, Kosovo, and Timor-Leste - and evaluates how these transitional administrations implemented their liberal mandates and how local involvement affected the conduct of their activities. In so doing, it reveals that these cases were neither liberal nor peacebuilding. It also demonstrates that while local involvement is imperative to peacebuilding, illiberal local involvement may prelude a return to an elite-centred status quo and reinforces or creates new forms of conflict and violence. Using both liberal and critical lenses, the author ultimately argues that the conceptual and operational departure from the holistic and comprehensive origins of liberal peacebuilding in fact paved the way for the crisis itself. Drawing on analysis from in-depth field research and interviews, this book will be of much interest to students of peacebuilding, peacekeeping, statebuilding, security studies and International Relations in general"-- Provided by publisher.
Locating a middle-ground between liberal and local trajectories in peacebuilding -- Cambodia : politicized involvement in a compromised peacebuilding -- Kosovo : superficial involvement in a co-opted peacebuilding -- Timor-Leste : exclusive involvement in a fragile peacebuilding -- The perils of liberal peacebuilding and pitfalls of local involvement.
Includes bibliographical references and index.
Keywords: Electronic books; Peace-building.; Liberalism